2021
DOI: 10.1111/tri.14147
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and patient satisfaction with outpatient care after heart transplantation in adult and pediatric patients – room for improvement?

Abstract: Summary Reduced adherence after heart transplantation increases the risk for acute rejection. Therefore, the aim of this study was to evaluate the patient’s satisfaction with outpatient care and quality of life (QOL) after pediatric and adult heart transplantation. Observational study after pediatric (n = 22) and adult (n = 65) heart transplantation and the parents of the pediatric patients (n = 22) to evaluate the patients’ satisfaction with outpatient care and QOL. Established standardized questionnaires wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Schmidthausen et al even concluded that QoL after pediatric heart transplantation is comparable to a standardized reference population in our country [ 1 ].…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…Schmidthausen et al even concluded that QoL after pediatric heart transplantation is comparable to a standardized reference population in our country [ 1 ].…”
mentioning
confidence: 88%
“…We read with great interest the article by colleagues Schmithausen et al on quality of life (QoL) and satisfaction with outpatient follow-up of patients after heart transplantation [ 1 ]. The authors reported on 205 patients who underwent heart transplantation and are seen regularly on an outpatient basis.…”
mentioning
confidence: 99%
See 2 more Smart Citations